Crucial Dimension in Organization Management of Indonesian Islamic Almsgiving (Zakah) Institutions: Insights for Community Economic Empowerment - Machdum, Sari Viciawati; Daryanti, Sri; Imelda, Johanna Debora; Adi, Isbandi Rukminto (The South East Asian Journal of Management, 2015)
This research analyzed the crucial management dimensions or key elements oforganizations that have been managed as Islamic almsgiving institutions (zakahfunds) in Indonesia. Zakah funds are traditionally managed for a limited number ofbeneficiaries. Zakah funds are now collected and managed by professional Islamicor faith-based organizations and institutions at the national or regional level toachieve a wider range of beneficiaries. This article examines how two Islamicor faith-based organizations, herein named CV (commanditaire vennootschap)“X” and “Y” Foundation, manage small enterprise programs based on zakah toreach a wider range of beneficiaries. Using qualitative methods, the researchidentifies crucial dimensions in the management of organizational dynamics ofthese Islamic or faith-based organizations, i.e., organizational systems, humanresources, and organizational climate. Those elements are used to manageeconomic empowerment activities with faith as a supra structure or contextualunderlying factor. Field findings also demonstrated the usefulness of religiousvalues in managing sustainable community-empowerment practices in smallenterprise programs.